Modified asphalt mixture for heavy-duty pavement and preparation method of modified asphalt mixture

By using reinforced fiber technology of sepiolite fiber and calcium sulfate whiskers in modified asphalt mixture for heavy-duty pavement, and combining modified polymers and liquid rubber to coat lignin particles, the existing mixture has solved the problems of high porosity, low saturation and poor dynamic stability, and high pressure resistance, crack resistance and long-life pavement materials are achieved.

CN119874260APending Publication Date: 2025-04-25广东省路桥建设发展有限公司 +1

Patent Information

Application Number
CN202510175576.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-18
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing modified asphalt mixture for heavy-load pavement has problems such as high porosity, low saturation and poor dynamic stability, which leads to poor pressure resistance of the pavement under heavy-load conditions, which easily leads to ruts and damage such as cracks during long-term use.

Method used

Sepiolite fiber and calcium sulfate whiskers are used as reinforcement fibers, and the compatibility between fiber and asphalt is improved through the dispersion of polyoxyethylene sorbitan fatty acid esters and the surface coating technology of diphenylmethane diisocyanate. Meanwhile, modified styrene-butadiene-styrene block copolymer and liquid rubber are used to coat lignin particles to enhance the toughness and elasticity of the mixture.

Benefits of technology

It realizes a modified asphalt mixture for heavy-duty pavement with low porosity, high saturation and high dynamic stability, which significantly improves the pressure resistance and crack resistance of the pavement and extends the service life of the pavement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a modified asphalt mixture for a heavy-duty pavement and a preparation method thereof, and belongs to the technical field of asphalt, the modified asphalt mixture for the heavy-duty pavement is composed of modified asphalt for the heavy-duty pavement and aggregate, and the mass ratio of the modified asphalt for the heavy-duty pavement to the aggregate is (6-13): 100; according to the modified asphalt mixture for the heavy-duty pavement, the dynamic stability at the temperature of 60 DEG C is 10076-10291 times / mm, the four-point bending fatigue life under the conditions of 15 DEG C, 10 Hz and 1000 epsilon mu is 98789-100342 / 1000 epsilon mu, the low-temperature bending test breaking strain at the temperature of-10 DEG C is 6152-6492 mu epsilon, the rut stripping area rate after water immersion in 50 hours is 0, the porosity is 1.41-1.65%, and the saturation degree is 74-79%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a modified asphalt mixture for heavy-load pavement and a preparation method thereof, belonging to the technical field of asphalt. Background Art

[0002] Most of the roads in my country are made of asphalt concrete pavement. Asphalt concrete pavement has good mechanical properties, good durability and driving comfort, and is suitable for the passage of various vehicles. The asphalt in asphalt concrete pavement is an important material that affects the long-term performance of the pavement. Among them, ordinary asphalt as a binder has problems such as low viscosity, insufficient aggregate coating thickness, and low pavement durability under heavy traffic. In recent years, with the increasing traffic loads of multiple axles, heavy axle loads, and high wheel pressures, as well as the large-scale construction of new expressways, a large number of initial damages have occurred on the pavement, and the road construction materials for heavy-loaded pavements are facing huge challenges. In order to meet the needs of heavy-loaded pavements, modified asphalt and modified asphalt mixtures prepared with modified asphalt have become a hot topic in the field of asphalt concrete pavement materials.

[0003] Chinese patent CN109761541A discloses an asphalt mixture for heavy-load traffic pavement and its processing technology, which uses polytetrafluoroethylene fiber to modify asphalt. The patent aims at the problem that the wear resistance and mechanical properties of asphalt mixture are relatively poor due to the poor wear resistance, low hardness and poor dimensional stability of polytetrafluoroethylene fiber. By adding nano-silicon dioxide to asphalt and filling nano-silicon dioxide into polytetrafluoroethylene fiber, its thermal conductivity is appropriately improved, the creep resistance of polytetrafluoroethylene fiber is improved, and large-area strip-shaped wear debris is avoided in the friction process of asphalt mixture, and its wear resistance is improved. The asphalt mixture prepared by the patent has outstanding wear resistance, but the porosity and saturation indexes are very poor, the compressive strength under heavy load is definitely not particularly good, and rutting is easy to form. Under long-term use, cracks and other damages are easy to occur. In addition, the polytetrafluoroethylene fiber and nano-silicon dioxide added are relatively expensive, and its economic efficiency is relatively poor when used on a large scale for pavement materials.

[0004] Chinese patent CN116161903A discloses an asphalt mixture suitable for heavy-duty traffic pavement and a heavy-duty pavement construction method. The asphalt mixture includes the following raw materials in parts by weight: 12-15 parts of asphalt, 68-75 parts of coarse aggregate, 15-18 parts of fine aggregate, 8-12 parts of mineral powder, 3-6 parts of lignin fiber, 3-5 parts of transparent powder-modified polyvinyl alcohol, 1-3 parts of polytetrafluoroethylene fiber, 1-2 parts of hollow glass microspheres, 3-5 parts of compatibilizer, 0.8-1.2 parts of amine antioxidant, and 1-2 parts of polyacrylaldehyde microspheres. The asphalt mixture obtained in this patent for heavy-duty traffic pavement has high porosity and low saturation, and its dynamic stability is also relatively poor, so its life span is bound to be relatively short under long-term use.

[0005] From the above, it can be seen that the modified asphalt mixture for heavy-duty pavement still has problems such as high porosity, low saturation, and poor dynamic stability. Therefore, the development of modified asphalt mixture for heavy-duty pavement with low porosity, high saturation and high dynamic stability has a very direct practical significance for improving the quality of road materials. Summary of the invention

[0006] In view of the deficiencies in the above-mentioned prior art, the present invention provides a modified asphalt mixture for heavy-loaded pavement and a preparation method thereof, so as to achieve the following invention objectives: to prepare a modified asphalt mixture for heavy-loaded pavement with low porosity, high saturation and high dynamic stability.

[0007] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions: A modified asphalt mixture for heavy-load pavement and a preparation method thereof, wherein the modified asphalt mixture for heavy-load pavement is composed of modified asphalt for heavy-load pavement and aggregate, and the mass ratio of the modified asphalt for heavy-load pavement to the aggregate is 6-13:100; The aggregate is a stone material that meets the intermediate grade standard of "Technical Specification for Highway Asphalt Pavement Construction JTG F40-2004", specifically including 1# material with a particle size of 0.1~3mm, 2# material with a particle size of 3~5mm, 3# material with a particle size of 5~10mm, and 4# material with a particle size of 10~15mm; The mass ratio of the 1# material, 2# material, 3# material and 4# material is 9~15:3~7:30~40:25~40; The specific formula of the modified asphalt for heavy-duty pavement is, in parts by weight: 190~260 parts of road petroleum asphalt, Modified reinforcing fiber 40~90 parts, Modified styrene-butadiene-styrene block copolymer (SBS) 20-45 parts, 50~80 parts of rubber powder, 25~50 parts of vegetable oil, 5-13 parts of liquid rubber coated lignin particles; The road petroleum asphalt is No. 70 asphalt or No. 90 asphalt specified in JTGF40-2019 "Technical Specifications for Highway Asphalt Pavement Construction"; The rubber powder is waste tire rubber powder with a particle size of 100-600 meshes; The vegetable oil is a mixture of tung oil and palm oil, and the mass ratio of tung oil to palm oil is 1-13:4; The following are further improvements to the above technical solution: Step 1: Preparation of modified reinforcing fibers After drying the sepiolite fiber and calcium sulfate whisker in an oven at 90-120°C for 8-13 hours, the fibers are added to a reactor, followed by adding toluene and polyoxyethylene sorbitan fatty acid ester, stirring is started, and the stirring rate is controlled at 1500-4000 rpm. After strong stirring and dispersion for 6-10 hours, the stirring rate is reduced to 800-1300 rpm, and the temperature is raised and kept constant at 80-110°C. Diphenylmethane diisocyanate is then added, and after stirring for 10-20 minutes, dibutyltin dilaurate is added. Under condensation reflux, the reaction is stirred at a constant temperature for 5-9 hours, and then a hydrocarbon primary amine is added. After the reaction is continued at a constant temperature for 2-6 hours, the reaction is centrifuged, and the separated solid is washed 2-4 times with anhydrous ethanol, and the modified reinforced fiber is obtained after natural drying. The hydrocarbon primary amine substance is one of dodecyl primary amine, tetradecyl primary amine, hexadecyl primary amine, 7-octen-1-amine, 2-cyclohexene-1-amine, and 1-amino-10-undecene; The diameter of the sepiolite fiber is 4-15 μm and the length is 3-15 mm; The diameter of the calcium sulfate whisker is 1-10 μm and the length is 40-400 μm; The mass ratio of the sepiolite fiber, calcium sulfate whisker, toluene, polyoxyethylene sorbitan fatty acid ester, diphenylmethane diisocyanate, dibutyltin dilaurate, and hydrocarbon primary amine substances is 30-90:6-20:150-220:1-2.5:6-18:0.2-0.8:5-15.

[0008] Step 2: Preparation of modified styrene-butadiene-styrene block copolymer After the styrene-butadiene-styrene block copolymer is cut into small pieces, it is placed in a 50-75°C oven and dried for 10-16 hours, and then transferred to a reactor, nitrogen is passed to replace the air in the reactor and the nitrogen protection state is maintained, toluene is added to the reactor, stirring is started, and after the styrene-butadiene-styrene block copolymer is completely dissolved, 2-octenyl succinic anhydride is added, and then the stirring rate is controlled at 400-1000 rpm, the temperature of the material in the reactor is increased and kept constant at 70-85°C, benzoyl peroxide is added, and the reaction is stirred at a constant temperature for 4-7 hours, and hydroquinone is added to terminate the reaction, and the stirring is continued until the material in the reactor is cooled to room temperature, and a precipitant anhydrous ethanol is added to the reactor, and after stirring for 30-60 minutes, the material is discharged and filtered, and the filtered solid is washed 2-3 times with a detergent anhydrous ethanol, and then dried naturally to obtain a modified styrene-butadiene-styrene block copolymer; The styrene-butadiene-styrene block copolymer has a melt flow index of 2-10 g / min at 200° C. and 5 kg, and a viscosity of a 25 wt% toluene solution thereof at 25° C. is 2000-6000 cps at 25° C.; The mass ratio of the styrene-butadiene-styrene block copolymer, toluene, 2-octenyl succinic anhydride, benzoyl peroxide, hydroquinone and precipitant anhydrous ethanol is 40-80:130-200:8-20:0.1-0.6:0.1-0.2:40-100.

[0009] Step 3: Preparation of liquid rubber-coated lignin particles After drying the lignin powder at 100-130°C for 8-15 hours, the powder is placed in a high-speed dispersion kettle, and then toluene and polyoxyethylene cetyl alcohol ether are added, and the dispersion rate is controlled at 8000-13000 rpm. After high-speed dispersion for 7-12 hours, the dispersion rate is reduced to 3000-4500 rpm, and then the temperature is raised and kept constant at 75-90°C, and then diphenylmethane diisocyanate and dibutyltin dilaurate are added. After constant temperature reaction for 5-9 hours, liquid rubber is added, and constant temperature reaction is continued for 4-7 hours, and then the material is cooled to room temperature for discharging and filtering. The filtered solid is washed with anhydrous ethanol for 2-4 times and dried naturally to obtain liquid rubber-coated lignin particles; The particle size of the lignin powder is 0.5-9 μm; The mass ratio of the lignin powder, toluene, polyoxyethylene cetyl alcohol ether, diphenylmethane diisocyanate, dibutyltin dilaurate, and liquid rubber is 40-90:150-300:1-5:15-50:0.3-0.9:8-20; The liquid rubber is hydroxyl-terminated polybutadiene; The hydroxyl-terminated polybutadiene has a hydroxyl value of 0.5-0.8 mmol / g, a viscosity of 3-8 Pa·s at 40° C., and a number average molecular weight of 2.5-4×10 3 g / mol.

[0010] Step 4: Preparation of modified asphalt for heavy-duty pavement According to the specific formula of modified asphalt for heavy-load road surface in parts by weight, first put vegetable oil and rubber powder into a mixing kettle with a high-speed stirring paddle and a high-speed dispersing paddle, heat to 130-180°C, turn on the high-speed dispersing paddle, control the shear dispersion rate at 6000-10000 rpm, after shear dispersion treatment for 100-180 minutes, stop the high-speed dispersing paddle, turn on the high-speed stirring paddle, control the stirring rate at 1000-2500 rpm, add road petroleum asphalt, and stop high-speed stirring after the road petroleum asphalt is completely melted. paddle, start the high-speed dispersing paddle, control the shear dispersion rate at 6000-10000 rpm, continue the shear dispersion treatment for 80-150 minutes, stop the high-speed dispersing paddle, start the high-speed stirring paddle, control the stirring rate at 2000-4500 rpm, add modified reinforcing fiber, modified styrene-butadiene-styrene block copolymer and liquid rubber coated lignin particles, continue stirring for 10-20 hours, cool to 65-85°C and then discharge, cool to room temperature after discharging, and obtain modified asphalt for heavy-load pavement.

[0011] Step 5: Preparation of modified asphalt mixture for heavy-duty pavement Aggregates should be graded and mixed in advance, and then modified asphalt for heavy-load pavement is added into the mixing kettle. The stirring rate is controlled at 500-1000 rpm and heated. The asphalt in the kettle is heated and kept at a constant temperature of 150-190°C. Aggregates are then added into the mixing kettle at a mass ratio of modified asphalt for heavy-load pavement to aggregate of 6-13:100. After stirring and mixing for 2-5 hours, the modified asphalt mixture for heavy-load pavement directly used for pavement paving is obtained.

[0012] Compared with the prior art, the present invention achieves the following beneficial effects: 1. The present invention uses sepiolite fibers and calcium sulfate whiskers with excellent mechanical properties to improve the mechanical properties of asphalt mixtures. The compatibility of the above two inorganic fibers with asphalt organic matter is relatively poor, and dispersion uniformity is a key problem that must be solved. In order to promote the compatibility of sepiolite fibers and calcium sulfate whiskers with asphalt and ensure the uniformity of dispersion, the present invention first disperses sepiolite fibers and calcium sulfate whiskers in a toluene solution under the dispersing effect of the dispersant polyoxyethylene sorbitan fatty acid ester using a long-term high-speed stirring process, and then uses diphenylmethane diisocyanate to coat the dispersed sepiolite fibers and calcium sulfate whiskers on the surface. After coating with isocyanate, a hydrocarbon primary amine substance with relatively good hydrophobic and lipophilic properties is added to react with the isocyanate, so that the outermost layer of the sepiolite fibers and calcium sulfate whiskers is coated with a layer of hydrocarbon primary amine substances, and the hydrophobic and lipophilic hydrocarbon groups are exposed on the surface, which greatly improves the compatibility of sepiolite fibers and calcium sulfate whiskers with the asphalt matrix and ensures the reinforcing effect of the reinforcing fiber on the asphalt mixture; 2. The present invention uses 2-octenyl succinic anhydride to modify styrene-butadiene-styrene block copolymer (SBS), thereby increasing the polarity of SBS and making SBS more compatible with asphalt matrix containing trace amounts of hydroxyl and carboxyl groups at the end, thereby maximizing the toughening effect of SBS on asphalt mixtures and promoting the low-temperature toughness and fatigue strength of asphalt mixtures under heavy loads; 3. The present invention first uses polyoxyethylene cetyl alcohol ether as a dispersant and combines it with a high-speed dispersion process to evenly disperse the lignin powder into a toluene solvent, then uses diphenylmethane diisocyanate to perform a surface coating of the lignin powder particles in a chemically bonded form, and then uses terminal hydroxyl polybutadiene to perform a second coating. The compatibility of the lignin powder particles coated with terminal hydroxyl polybutadiene with asphalt is substantially improved. When the asphalt mixture is mixed, the lignin powder particles coated with terminal hydroxyl polybutadiene can construct a buffer transition layer with rubber elasticity between the asphalt matrix and the aggregate particles, which can greatly enhance the toughness and elasticity of the asphalt mixture, and thus can greatly improve the low-temperature mechanical properties and crack resistance of the asphalt mixture under heavy loads; 4. The present invention uses a mixed vegetable oil composed of tung oil and palm oil and combines it with a high-speed shear dispersion process to pre-disperse and swell the rubber powder. The combination of the two vegetable oils is close to the polarity of the rubber powder, which can ensure that the vegetable oil molecules penetrate and thermally erode the vulcanized cross-linked network inside the rubber powder particles under high temperature and strong shear, promote the thermal dissociation of the vulcanized cross-linked network of the rubber powder, and then promote the close bonding between the rubber powder and asphalt when the two are melt-blended, and finally ensure that the rubber powder plays a toughening role on the asphalt mixture; 5. The modified asphalt mixture for heavy-load pavement prepared by the present invention has a dynamic stability of 10076~10291 times / mm at 60°C, a four-point bending fatigue life of 98789~100342 / 1000εμ under the conditions of 15°C, 10Hz, and 1000εμ, a failure strain of 6152~6492με in a low-temperature bending test at -10°C, a 50h immersion rutting stripping area rate of 0, a porosity of 1.41~1.65%, and a saturation of 74~79%. DETAILED DESCRIPTION

[0013] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0014] Example 1: A method for preparing a modified asphalt mixture for heavy-duty pavement Step 1: Preparation of modified reinforcing fibers After the sepiolite fiber and calcium sulfate whisker were placed in an oven at 100° C. and dried for 11 hours, they were added to a reactor, and then toluene and polyoxyethylene sorbitan fatty acid ester were added, stirring was started, and the stirring rate was controlled at 2500 rpm. After strong stirring and dispersion for 9 hours, the stirring rate was reduced to 1100 rpm, and then the temperature was raised and kept constant at 100° C., and then diphenylmethane diisocyanate was added. After stirring for 18 minutes, dibutyltin dilaurate was added. Under condensation reflux, the reaction was stirred at a constant temperature for 8 hours, and then a hydrocarbon primary amine substance was added. After the reaction was continued at a constant temperature and stirred for 4 hours, the reaction was centrifuged, and the separated solid was washed 3 times with anhydrous ethanol, and the modified reinforced fiber was obtained after natural drying; The hydrocarbon primary amine substance is dodecyl primary amine; The sepiolite fiber has a diameter of 6 μm and a length of 9 mm; The diameter of the calcium sulfate whisker is 5 μm and the length is 130 μm; The mass ratio of the sepiolite fiber, calcium sulfate whisker, toluene, polyoxyethylene sorbitan fatty acid ester, diphenylmethane diisocyanate, dibutyltin dilaurate, and hydrocarbon primary amine substances is 65:13:200:2:11:0.6:11.

[0015] Step 2: Preparation of modified styrene-butadiene-styrene block copolymer After the styrene-butadiene-styrene block copolymer is cut into small pieces, it is placed in a 70° C. oven and dried for 12 hours, and then transferred to a reactor, nitrogen is passed through to replace the air in the reactor and the nitrogen protection state is maintained, toluene is added to the reactor, stirring is started, and after the styrene-butadiene-styrene block copolymer is completely dissolved, 2-octenyl succinic anhydride is added, and then the stirring rate is controlled at 700 rpm, the temperature of the material in the reactor is raised and kept constant at 80° C., benzoyl peroxide is added, and the reaction is stirred at a constant temperature for 6 hours, and then hydroquinone is added to terminate the reaction, and the stirring is continued until the material in the reactor is cooled to room temperature, and then anhydrous ethanol as a precipitant is added to the reactor, and after stirring for 50 minutes, the material is discharged and filtered, and the filtered solid is washed twice with anhydrous ethanol as a detergent, and then dried naturally to obtain a modified styrene-butadiene-styrene block copolymer; The styrene-butadiene-styrene block copolymer has a melt flow index of 8 g / min at 200° C. and 5 kg, and a viscosity of a 25 wt % toluene solution thereof at 25° C. is 4500 cps; The mass ratio of the styrene-butadiene-styrene block copolymer, toluene, 2-octenylsuccinic anhydride, benzoyl peroxide, hydroquinone, and precipitant anhydrous ethanol is 65:170:12:0.5:0.13:80.

[0016] Step 3: Preparation of liquid rubber-coated lignin particles After drying the lignin powder at 120° C. for 11 hours, the powder was placed in a high-speed dispersion kettle, and then toluene and polyoxyethylene cetyl alcohol ether were added, and the dispersion rate was controlled at 9000 rpm. After 11 hours of high-speed dispersion, the dispersion rate was reduced to 4000 rpm, and then the temperature was raised and kept constant at 80° C., and then diphenylmethane diisocyanate and dibutyltin dilaurate were added. After constant temperature reaction for 8 hours, liquid rubber was added, and the constant temperature reaction was continued for 6 hours, and then the material was cooled to room temperature, discharged, filtered, and the filtered solid was washed with anhydrous ethanol for 3 times, and then naturally dried to obtain liquid rubber-coated lignin particles; The particle size of the lignin powder is 2 μm; The mass ratio of the lignin powder, toluene, polyoxyethylene cetyl alcohol ether, diphenylmethane diisocyanate, dibutyltin dilaurate, and liquid rubber is 70:200:4:30:0.7:15; The liquid rubber is hydroxyl-terminated polybutadiene; The hydroxyl value of the hydroxy-terminated polybutadiene is 0.7 mmol / g, the viscosity at 40°C is 4 Pa·s, and the number average molecular weight is 3×10 3 g / mol.

[0017] Step 4: Preparation of modified asphalt for heavy-duty pavement The specific formula of the modified asphalt for heavy-duty pavement is, in parts by weight: 200 parts of road petroleum asphalt, Modified reinforcing fiber 50 parts, Modified styrene-butadiene-styrene block copolymer (SBS) 40 parts, 70 parts of rubber powder, 35 parts vegetable oil, 8 parts of liquid rubber coated lignin particles; The road petroleum asphalt is No. 70 asphalt specified in JTGF40-2019 "Technical Specifications for Highway Asphalt Pavement Construction"; The rubber powder is waste tire rubber powder with a particle size of 300 meshes; The vegetable oil is a mixture of tung oil and palm oil, and the mass ratio of tung oil to palm oil is 6:4; According to the specific formula of modified asphalt for heavy-loaded pavement in parts by weight, vegetable oil and rubber powder are first put into a mixing kettle with a high-speed stirring paddle and a high-speed dispersing paddle, heated to 140°C, the high-speed dispersing paddle is turned on, the shear dispersion rate is controlled at 9000 rpm, and after shear dispersion treatment for 150 minutes, the high-speed dispersing paddle is stopped, the high-speed stirring paddle is turned on, the stirring rate is controlled at 1500 rpm, and road petroleum asphalt is added. After the road petroleum asphalt is completely melted, the high-speed stirring paddle is stopped, the high-speed dispersing paddle is turned on, the shear dispersion rate is controlled at 9000 rpm, and the shear dispersion treatment is continued for 120 minutes. The high-speed dispersing paddle is stopped, the high-speed stirring paddle is turned on, the stirring rate is controlled at 3500 rpm, and modified reinforcing fiber, modified styrene-butadiene-styrene block copolymer and liquid rubber coated lignin particles are added. After continuous stirring for 17 hours, the material is cooled to 80°C and then discharged. After the material is discharged, it is cooled to room temperature to obtain modified asphalt for heavy-loaded pavement.

[0018] Step 5: Preparation of modified asphalt mixture for heavy-duty pavement Aggregates are graded and mixed well in advance, and then modified asphalt for heavy-duty pavement is added to the mixing kettle, and the stirring rate is controlled at 800 rpm, and the asphalt in the kettle is heated and kept at 160°C. Then, according to the mass ratio of modified asphalt for heavy-duty pavement to aggregate being 11:100, the aggregate is added to the mixing kettle, and after stirring and mixing for 4 hours, the modified asphalt mixture for heavy-duty pavement directly used for pavement is obtained; The aggregate is a stone material that meets the medium-grade standard of "Technical Specification for Highway Asphalt Pavement Construction JTG F40-2004", specifically including 1# material with a particle size of 1mm, 2# material with a particle size of 4mm, 3# material with a particle size of 8mm, and 4# material with a particle size of 14mm; The mass ratio of the 1# material, 2# material, 3# material and 4# material is 11:4:37:37.

[0019] Example 2: A method for preparing a modified asphalt mixture for heavy-duty pavement Step 1: Preparation of modified reinforcing fibers After the sepiolite fiber and calcium sulfate whisker were dried in a 90°C oven for 8 hours, they were added to a reactor, and then toluene and polyoxyethylene sorbitan fatty acid ester were added, stirring was started, and the stirring rate was controlled at 1500 rpm. After strong stirring and dispersion for 6 hours, the stirring rate was reduced to 800 rpm, and then the temperature was raised and kept constant at 80°C, and then diphenylmethane diisocyanate was added. After stirring for 10 minutes, dibutyltin dilaurate was added, and the reaction was stirred at a constant temperature for 5 hours under condensation reflux, and then a hydrocarbon primary amine substance was added. After the reaction was continued at a constant temperature and stirred for 2 hours, the separated solid was washed twice with anhydrous ethanol, and the modified reinforced fiber was obtained after natural drying; The hydrocarbon primary amine substance is tetradecyl primary amine; The sepiolite fiber has a diameter of 4 μm and a length of 3 mm; The diameter of the calcium sulfate whisker is 1 μm and the length is 40 μm; The mass ratio of the sepiolite fiber, calcium sulfate whisker, toluene, polyoxyethylene sorbitan fatty acid ester, diphenylmethane diisocyanate, dibutyltin dilaurate, and hydrocarbon primary amine substances is 30:6:150:1:6:0.2:5.

[0020] Step 2: Preparation of modified styrene-butadiene-styrene block copolymer After the styrene-butadiene-styrene block copolymer is cut into small pieces, the pieces are placed in a 50° C. oven for drying for 10 hours, and then the pieces are transferred to a reactor. The air in the reactor is replaced by nitrogen and the nitrogen protection state is maintained. Toluene is added to the reactor and stirring is started. After the styrene-butadiene-styrene block copolymer is completely dissolved, 2-octenyl succinic anhydride is added, and then the stirring rate is controlled at 400 rpm. The temperature of the material in the reactor is raised and kept constant at 70° C. Benzoyl peroxide is added, and the reaction is stirred at a constant temperature for 4 hours. Hydroquinone is added to terminate the reaction. After the material in the reactor is cooled to room temperature, anhydrous ethanol as a precipitant is added to the reactor. After stirring for 30 minutes, the material is discharged and filtered. The filtered solid is washed twice with anhydrous ethanol as a detergent and dried naturally to obtain a modified styrene-butadiene-styrene block copolymer. The styrene-butadiene-styrene block copolymer has a melt flow index of 2 g / min at 200° C. and 5 kg, and a viscosity of a 25 wt % toluene solution thereof at 25° C. is 2000 cps; The mass ratio of the styrene-butadiene-styrene block copolymer, toluene, 2-octenylsuccinic anhydride, benzoyl peroxide, hydroquinone, and precipitant anhydrous ethanol is 40:130:8:0.1:0.1:40.

[0021] Step 3: Preparation of liquid rubber-coated lignin particles After drying the lignin powder at 100°C for 8 hours, the powder was placed in a high-speed dispersion kettle, and then toluene and polyoxyethylene cetyl alcohol ether were added, and the dispersion rate was controlled at 8000 rpm. After 7 hours of high-speed dispersion, the dispersion rate was reduced to 3000 rpm, and then the temperature was raised and kept constant at 75°C, and then diphenylmethane diisocyanate and dibutyltin dilaurate were added. After constant temperature reaction for 5 hours, liquid rubber was added, and the constant temperature reaction was continued for 4 hours, and then the temperature was reduced to room temperature, discharged, filtered, and the filtered solid was washed with anhydrous ethanol twice, and then naturally dried to obtain liquid rubber-coated lignin particles; The particle size of the lignin powder is 0.5 μm; The mass ratio of the lignin powder, toluene, polyoxyethylene cetyl alcohol ether, diphenylmethane diisocyanate, dibutyltin dilaurate, and liquid rubber is 40:150:1:15:0.3:8; The liquid rubber is hydroxyl-terminated polybutadiene; The hydroxyl value of the hydroxy-terminated polybutadiene is 0.5 mmol / g, the viscosity at 40°C is 3 Pa·s, and the number average molecular weight is 2.5×10 3 g / mol.

[0022] Step 4: Preparation of modified asphalt for heavy-duty pavement The specific formula of the modified asphalt for heavy-duty pavement is, in parts by weight: 190 parts of road petroleum asphalt, 40 parts of modified reinforcing fiber, Modified styrene-butadiene-styrene block copolymer (SBS) 20 parts, 50 parts of rubber powder, 25 parts vegetable oil, 5 parts of liquid rubber coated lignin particles; The road petroleum asphalt is No. 90 asphalt specified in JTGF40-2019 "Technical Specifications for Highway Asphalt Pavement Construction"; The rubber powder is waste tire rubber powder with a particle size of 100 meshes; The vegetable oil is a mixture of tung oil and palm oil, and the mass ratio of tung oil to palm oil is 1:4; According to the specific formula of modified asphalt for heavy-loaded pavement in parts by weight, vegetable oil and rubber powder are first put into a mixing kettle with a high-speed stirring paddle and a high-speed dispersing paddle, heated to 130°C, the high-speed dispersing paddle is turned on, the shear dispersion rate is controlled at 6000 rpm, after shear dispersion treatment for 100 minutes, the high-speed dispersing paddle is stopped, the high-speed stirring paddle is turned on, the stirring rate is controlled at 1000 rpm, and road petroleum asphalt is added. After the road petroleum asphalt is completely melted, the high-speed stirring paddle is stopped, the high-speed dispersing paddle is turned on, the shear dispersion rate is controlled at 6000 rpm, the shear dispersion treatment is continued for 80 minutes, the high-speed dispersing paddle is stopped, the high-speed stirring paddle is turned on, the stirring rate is controlled at 2000 rpm, and modified reinforcing fiber, modified styrene-butadiene-styrene block copolymer and liquid rubber coated lignin particles are added. After continuous stirring for 10 hours, the material is cooled to 65°C and then discharged. After discharging, the material is cooled to room temperature to obtain modified asphalt for heavy-loaded pavement.

[0023] Step 5: Preparation of modified asphalt mixture for heavy-duty pavement Aggregates are graded and mixed well in advance, and then modified asphalt for heavy-duty pavement is added into the mixing kettle, and the stirring rate is controlled at 500 rpm, and the asphalt in the kettle is heated and kept at 150°C, and then the aggregate is added into the mixing kettle at a mass ratio of modified asphalt for heavy-duty pavement to aggregate of 6:100, and after stirring and mixing for 2 hours, the modified asphalt mixture for heavy-duty pavement directly used for pavement is obtained; The aggregate is a stone material that meets the medium-grade standard of "Technical Specification for Highway Asphalt Pavement Construction JTG F40-2004", specifically including 1# material with a particle size of 0.1mm, 2# material with a particle size of 3mm, 3# material with a particle size of 5mm, and 4# material with a particle size of 10mm; The mass ratio of the 1# material, 2# material, 3# material and 4# material is 9:3:30:25.

[0024] Example 3: A method for preparing a modified asphalt mixture for heavy-duty pavement Step 1: Preparation of modified reinforcing fibers After the sepiolite fiber and calcium sulfate whisker were dried in an oven at 120° C. for 13 hours, they were added to a reactor, and then toluene and polyoxyethylene sorbitan fatty acid ester were added, stirring was started, and the stirring rate was controlled at 4000 rpm. After strong stirring and dispersion for 10 hours, the stirring rate was reduced to 1300 rpm, and then the temperature was raised and kept constant at 110° C., and then diphenylmethane diisocyanate was added. After stirring for 20 minutes, dibutyltin dilaurate was added. Under condensation reflux, the reaction was stirred at a constant temperature for 9 hours, and then a hydrocarbon primary amine substance was added. After the reaction was continued at a constant temperature for 6 hours, the reaction was centrifuged, and the separated solid was washed 4 times with anhydrous ethanol, and the modified reinforced fiber was obtained after natural drying; The hydrocarbon primary amine substance is hexadecyl primary amine; The sepiolite fiber has a diameter of 15 μm and a length of 15 mm; The calcium sulfate whisker has a diameter of 10 μm and a length of 400 μm; The mass ratio of the sepiolite fiber, calcium sulfate whisker, toluene, polyoxyethylene sorbitan fatty acid ester, diphenylmethane diisocyanate, dibutyltin dilaurate, and hydrocarbon primary amine substances is 90:20:220:2.5:18:0.8:15.

[0025] Step 2: Preparation of modified styrene-butadiene-styrene block copolymer After the styrene-butadiene-styrene block copolymer is cut into small pieces, the pieces are placed in a 75° C. oven for drying for 16 hours, and then the pieces are transferred to a reactor. The air in the reactor is replaced by nitrogen and the nitrogen protection state is maintained. Toluene is added to the reactor and stirring is started. After the styrene-butadiene-styrene block copolymer is completely dissolved, 2-octenyl succinic anhydride is added. Then, the stirring rate is controlled at 1000 rpm, the temperature of the material in the reactor is raised and kept constant at 85° C., benzoyl peroxide is added, and the reaction is stirred at a constant temperature for 7 hours. Hydroquinone is added to terminate the reaction. After the material in the reactor is cooled to room temperature, anhydrous ethanol as a precipitant is added to the reactor. After stirring for 60 minutes, the material is discharged and filtered. The filtered solid is washed 3 times with anhydrous ethanol as a detergent and dried naturally to obtain a modified styrene-butadiene-styrene block copolymer. The styrene-butadiene-styrene block copolymer has a melt flow index of 10 g / min at 200° C. and 5 kg, and a viscosity of a 25 wt % toluene solution thereof at 25° C. is 6000 cps; The mass ratio of the styrene-butadiene-styrene block copolymer, toluene, 2-octenylsuccinic anhydride, benzoyl peroxide, hydroquinone, and precipitant anhydrous ethanol is 80:200:20:0.6:0.2:100.

[0026] Step 3: Preparation of liquid rubber-coated lignin particles After drying the lignin powder at 130° C. for 15 hours, the powder was placed in a high-speed dispersion kettle, and then toluene and polyoxyethylene cetyl alcohol ether were added, and the dispersion rate was controlled at 13,000 rpm. After high-speed dispersion for 12 hours, the dispersion rate was reduced to 4,500 rpm, and then the temperature was raised and kept constant at 90° C., and then diphenylmethane diisocyanate and dibutyltin dilaurate were added. After constant temperature reaction for 9 hours, liquid rubber was added, and constant temperature reaction was continued for 7 hours, and then the material was cooled to room temperature, discharged, filtered, and the filtered solid was washed with anhydrous ethanol for 4 times, and then naturally dried to obtain liquid rubber-coated lignin particles; The particle size of the lignin powder is 9 μm; The mass ratio of the lignin powder, toluene, polyoxyethylene cetyl alcohol ether, diphenylmethane diisocyanate, dibutyltin dilaurate, and liquid rubber is 90:300:5:50:0.9:20; The liquid rubber is hydroxyl-terminated polybutadiene; The hydroxyl value of the hydroxy-terminated polybutadiene is 0.8 mmol / g, the viscosity at 40°C is 8 Pa·s, and the number average molecular weight is 4×10 3 g / mol.

[0027] Step 4: Preparation of modified asphalt for heavy-duty pavement The specific formula of the modified asphalt for heavy-duty pavement is, in parts by weight: 260 parts of road petroleum asphalt, Modified reinforcing fiber 90 parts, Modified styrene-butadiene-styrene block copolymer (SBS) 45 parts, 80 parts of rubber powder, 50 parts vegetable oil, 13 parts of liquid rubber coated lignin particles; The road petroleum asphalt is No. 90 asphalt specified in JTGF40-2019 "Technical Specifications for Highway Asphalt Pavement Construction"; The rubber powder is waste tire rubber powder with a particle size of 600 mesh; The vegetable oil is a mixture of tung oil and palm oil, and the mass ratio of tung oil to palm oil is 13:4; According to the specific formula of modified asphalt for heavy-loaded pavement in parts by weight, vegetable oil and rubber powder are first put into a mixing kettle with a high-speed stirring paddle and a high-speed dispersing paddle, heated to 180°C, the high-speed dispersing paddle is turned on, the shear dispersion rate is controlled at 10,000 rpm, and after shear dispersion treatment for 180 minutes, the high-speed dispersing paddle is stopped, the high-speed stirring paddle is turned on, the stirring rate is controlled at 2,500 rpm, and road petroleum asphalt is added. After the road petroleum asphalt is completely melted, the high-speed stirring paddle is stopped, the high-speed dispersing paddle is turned on, the shear dispersion rate is controlled at 10,000 rpm, the shear dispersion treatment is continued for 150 minutes, the high-speed dispersing paddle is stopped, the high-speed stirring paddle is turned on, the stirring rate is controlled at 4,500 rpm, and modified reinforcing fiber, modified styrene-butadiene-styrene block copolymer and liquid rubber coated lignin particles are added. After continuous stirring for 20 hours, the material is cooled to 85°C and then discharged. After the material is discharged, it is cooled to room temperature to obtain modified asphalt for heavy-loaded pavement.

[0028] Step 5: Preparation of modified asphalt mixture for heavy-duty pavement Aggregates are graded and mixed well in advance, and then modified asphalt for heavy-duty pavement is added to the mixing kettle, and the stirring rate is controlled at 1000 rpm, and the asphalt in the kettle is heated and kept at 190°C, and then the aggregate is added to the mixing kettle at a mass ratio of modified asphalt for heavy-duty pavement to aggregate of 13:100, and after stirring and mixing for 5 hours, the modified asphalt mixture for heavy-duty pavement directly used for pavement is obtained; The aggregate is a stone material that meets the medium-grade standard of "Technical Specification for Highway Asphalt Pavement Construction JTG F40-2004", specifically including 1# material with a particle size of 3mm, 2# material with a particle size of 5mm, 3# material with a particle size of 10mm, and 4# material with a particle size of 15mm; The mass ratio of the 1# material, 2# material, 3# material and 4# material is 15:7:40:40.

[0029] Example 4: A method for preparing a modified asphalt mixture for heavy-duty pavement Step 1: Preparation of modified reinforcing fibers The hydrocarbon primary amine substance is 7-octen-1-amine, and the other operations are the same as in Example 1; The operations of steps 2, 3, 4 and 5 are the same as those of Example 1.

[0030] Example 5: A method for preparing a modified asphalt mixture for heavy-duty pavement Step 1: Preparation of modified reinforcing fibers The hydrocarbon primary amine substance is 2-cyclohexene-1-amine, and the other operations are the same as in Example 1; The operations of steps 2, 3, 4 and 5 are the same as those of Example 1.

[0031] Example 6: A method for preparing a modified asphalt mixture for heavy-load pavement Step 1: Preparation of modified reinforcing fibers The hydrocarbon primary amine substance is 1-amino-10-undecene, and the other operations are the same as in Example 1; The operations of steps 2, 3, 4 and 5 are the same as those of Example 1.

[0032] Comparative Example 1: Based on Example 1, step 1, preparation of modified reinforcing fiber, is not performed. In step 4, preparation of modified asphalt for heavy-duty road surface, modified reinforcing fiber is not added, and 50 parts of modified reinforcing fiber are replaced by 50 parts of road petroleum asphalt in equal amount. The specific operation is as follows: Step 1, preparation of modified reinforcing fiber is not performed; The operations of steps 2 and 3 are the same as those of Example 1; Step 4: Preparation of modified asphalt for heavy-duty pavement 50 parts of modified reinforcing fiber were replaced by 50 parts of road petroleum asphalt, and other operations were the same as in Example 1; The operation of step 5 is the same as that of embodiment 1.

[0033] Comparative Example 2: Based on Example 1, step 1, preparation of modified reinforcing fiber, is not performed. In step 4, preparation of modified asphalt for heavy-load road surface, 50 parts of modified reinforcing fiber are replaced by 50 parts of reinforcing fiber, and the reinforcing fiber consists of sepiolite fiber and calcium sulfate whisker, and the ratio of the two is the same as that in Example 1. The specific operation is as follows: Step 1, preparation of modified reinforcing fiber is not performed; The operations of steps 2 and 3 are the same as those of Example 1; Step 4: Preparation of modified asphalt for heavy-duty pavement 50 parts of the modified reinforcing fiber were replaced by 50 parts of the reinforcing fiber, and the other operations were the same as in Example 1; The reinforcing fibers are composed of sepiolite fibers and calcium sulfate whiskers, with a mass ratio of 65:13; The operation of step 5 is the same as that of embodiment 1.

[0034] Comparative Example 3: Based on Example 1, step 2, preparation of modified styrene-butadiene-styrene block copolymer, is not performed. In step 4, preparation of modified asphalt for heavy-load road surface, 40 parts of modified styrene-butadiene-styrene block copolymer are replaced by 40 parts of road petroleum asphalt in equal amounts. The specific operation is as follows: The operation of step 1 is the same as that of embodiment 1; Step 2, preparation of modified styrene-butadiene-styrene block copolymer is not performed; The operation of step 3 is the same as that of embodiment 1; Step 4: Preparation of modified asphalt for heavy-duty pavement 40 parts of modified styrene-butadiene-styrene block copolymer were replaced by 40 parts of road petroleum asphalt, and the other operations were the same as in Example 1; The operation of step 5 is the same as that of embodiment 1.

[0035] Comparative Example 4: Based on Example 1, step 3, preparation of liquid rubber-coated lignin particles, is not performed. In step 4, preparation of modified asphalt for heavy-duty road surface, 8 parts of liquid rubber-coated lignin particles are replaced by 8 parts of road petroleum asphalt in equal amounts. The specific operation is as follows: The operations of steps 1 and 2 are the same as those of Example 1; Step 3, preparation of liquid rubber-coated lignin particles, is not performed; Step 4: Preparation of modified asphalt for heavy-duty pavement 8 parts of liquid rubber coated lignin particles were replaced by 8 parts of road petroleum asphalt, and the other operations were the same as in Example 1; The operation of step 5 is the same as that of embodiment 1.

[0036] Comparative Example 5: Based on Example 1, step 3, preparation of liquid rubber-coated lignin particles, is not performed. In step 4, preparation of modified asphalt for heavy-load road surface, 8 parts of liquid rubber-coated lignin particles are replaced by 8 parts of lignin powder in equal amounts. The specific operation is as follows: The operations of steps 1 and 2 are the same as those of Example 1; Step 3, preparation of liquid rubber-coated lignin particles, is not performed; Step 4: Preparation of modified asphalt for heavy-duty pavement 8 parts of liquid rubber coated lignin particles were replaced by 8 parts of lignin powder, and the other operations were the same as in Example 1; The particle size of the lignin powder is 2 μm; The operation of step 5 is the same as that of embodiment 1.

[0037] Comparative Example 6: Based on Example 1, in step 4, in the preparation of modified asphalt for heavy-duty road surface, 35 parts of vegetable oil were replaced with 35 parts of road petroleum asphalt. The specific operation was as follows: The operations of steps 1, 2, and 3 are the same as those of Example 1; Step 4: Preparation of modified asphalt for heavy-duty pavement The specific formula of the modified asphalt for heavy-duty pavement is, in parts by weight: 235 parts of road petroleum asphalt, Modified reinforcing fiber 50 parts, Modified styrene-butadiene-styrene block copolymer (SBS) 40 parts, 70 parts of rubber powder, 8 parts of liquid rubber coated lignin particles; The road petroleum asphalt is No. 70 asphalt specified in JTGF40-2019 "Technical Specifications for Highway Asphalt Pavement Construction"; The rubber powder is waste tire rubber powder with a particle size of 300 meshes; According to the specific formula of modified asphalt for heavy-loaded pavement in parts by weight, firstly, put road petroleum asphalt and rubber powder into a mixing kettle with a high-speed stirring paddle and a high-speed dispersing paddle, control the stirring rate at 1500 rpm, heat to 140°C, and after the road petroleum asphalt is completely melted, stop the high-speed stirring paddle, start the high-speed dispersing paddle, control the shear dispersion rate at 9000 rpm, after shear dispersion treatment for 270 minutes, stop the high-speed dispersing paddle, start the high-speed stirring paddle, control the stirring rate at 3500 rpm, add modified reinforcing fiber, modified styrene-butadiene-styrene block copolymer and liquid rubber coated lignin particles, continue stirring for 17 hours, cool to 80°C and then discharge, and cool to room temperature after discharge to obtain modified asphalt for heavy-loaded pavement; The operation of step 5 is the same as that of embodiment 1.

[0038] Performance Test: According to the test method in JTG-E20-2011 "Test Procedure for Asphalt and Asphalt Mixtures for Highway Engineering", the modified asphalt mixtures for heavy-duty pavement obtained in Examples 1, 2, 3, 4, 5, 6 and Comparative Examples 1, 2, 3, 4, 5, 6 were tested for dynamic stability, four-point bending fatigue life, -10°C low-temperature bending test failure strain, 50h immersion rutting stripping area rate, porosity and saturation, and the results are shown in Table 1: Table 1

[0039]

[0040] From the data in Table 1, it can be seen that the dynamic stability of Examples 1-6 is all above 10,000 times / mm, the four-point bending fatigue life is also greater than 98,000, the -10°C low-temperature bending test failure strain is not less than 6100με, the 50h immersion rutting stripping area rate is 0, the porosity is within 1.7%, and the saturation is above 74%. The above indicators are relatively high, indicating that the modified asphalt mixture for heavy-load pavement obtained in Examples 1-6 has very excellent heavy-load road performance; Comparative Example 1, without adding modified reinforcing fiber or any unmodified reinforcing fiber, compared with Example 1, the dynamic stability of Comparative Example 1 is reduced by more than half, the four-point bending fatigue life and the -10°C low-temperature bending test failure strain are reduced by nearly half, and the 50h immersion rutting stripping area rate increases sharply to 19.5%, and there is no significant change in porosity and saturation, which shows that the addition of modified reinforcing fibers has a great improvement on the mechanical properties, fatigue resistance, low temperature and water immersion resistance of modified asphalt mixture for heavy-load pavement, and has little effect on porosity and saturation, which also shows that the modified reinforcing fibers can be very well dispersed in the asphalt matrix, and will not increase the porosity of the asphalt mixture and cause a decrease in the saturation of the asphalt mixture; the reinforcing fibers added in Comparative Example 2 have not been modified, and the mechanical properties of Comparative Example 2 are slightly better than those of Comparative Example 1, which shows that the unmodified reinforcing fibers can only slightly improve the asphalt mixture to a very limited extent. Mechanical properties, and the porosity of Example 2 is much greater than that of Example 1, and the saturation is significantly less than that of Example 1, which shows that the unmodified reinforcing fibers are difficult to be well dispersed in the asphalt matrix; Comparative Example 3 does not add modified styrene-butadiene-styrene block copolymer, and the mechanical properties indicators are significantly reduced, among which the four-point bending fatigue life and -10°C low-temperature bending test failure strain two indicators decreased significantly, the porosity, saturation and Example 1 are very small, which shows that the modified styrene-butadiene-styrene block copolymer has a very large effect on improving the toughness and low-temperature resistance of asphalt mixture; Comparative Example 4 does not add liquid The mechanical properties of Example 4 are significantly reduced, the porosity increases to a relatively high level, and the saturation drops to 65%, which indicates that the liquid rubber-coated lignin particles can improve the density of the asphalt mixture, reduce the porosity, and effectively improve the mechanical properties by increasing the saturation of the mixture itself; Example 5 does not use liquid rubber to coat the lignin, but directly adds lignin powder. Compared with Example 4, the mechanical properties of Example 5 are significantly lower than those of Example 4, and the 50h immersion rutting area rate increases to 8%. This may be because the uncoated lignin powder is very easy to absorb water, resulting in the lignin inside the asphalt mixture. The lignin powder absorbs too much water, which reduces the rutting resistance of the mixture. In addition, the porosity of Comparative Example 5 is higher than that of Comparative Example 4, and the saturation is significantly lower than that of Comparative Example 4. This may be due to the fact that the uncoated lignin powder is difficult to be evenly dispersed in the asphalt matrix; Comparative Example 6 does not add vegetable oil, and all the indicators listed in the table drop to the worst value. This may be because vegetable oil can promote the swelling of rubber powder and the uniformity of the dispersion of rubber powder particles in the asphalt matrix after swelling. Without vegetable oil, the rubber powder is difficult to swell and difficult to be effectively sheared, so it is difficult to mix with the asphalt matrix into a uniform and stable homogeneous substance, which leads to a comprehensive decline in the performance of the asphalt mixture.

[0041] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A modified asphalt mixture for heavy-load pavement, characterized in that: The modified asphalt mixture for heavy-duty pavement is composed of modified asphalt for heavy-duty pavement and aggregate, and the mass ratio of the modified asphalt for heavy-duty pavement to the aggregate is 6-13:100; The aggregate is a stone material that meets the intermediate grade standard of "Technical Specification for Highway Asphalt Pavement Construction JTG F40-2004", specifically including 1# material with a particle size of 0.1~3mm, 2# material with a particle size of 3~5mm, 3# material with a particle size of 5~10mm, and 4# material with a particle size of 10~15mm; The mass ratio of the 1# material, 2# material, 3# material and 4# material is 9~15:3~7:30~40:25~40; The specific formula of the modified asphalt for heavy-duty pavement is, in parts by weight: 190~260 parts of road petroleum asphalt, Modified reinforcing fiber 40~90 parts, Modified styrene-butadiene-styrene block copolymer (SBS) 20-45 parts, 50~80 parts of rubber powder, 25~50 parts of vegetable oil, 5-13 parts of liquid rubber coated lignin particles; The road petroleum asphalt is No. 70 asphalt or No. 90 asphalt specified in JTGF40-2019 "Technical Specifications for Highway Asphalt Pavement Construction"; The rubber powder is waste tire rubber powder with a particle size of 100-600 meshes; The vegetable oil is a mixture of tung oil and palm oil, and the mass ratio of tung oil to palm oil is 1-13:4; The modified reinforced fiber is prepared by: placing sepiolite fiber and calcium sulfate whisker in an oven at 90-120°C and drying for 8-13 hours, adding them to a reaction kettle, then adding toluene and polyoxyethylene sorbitan fatty acid ester, starting stirring, controlling the stirring rate at 1500-4000 rpm, vigorously stirring and dispersing for 6-10 hours, reducing the stirring rate to 800-1300 rpm, then heating and keeping the temperature constant at 80-110°C, then adding diphenylmethane diisocyanate, stirring for 10-20 minutes, then adding dibutyltin dilaurate, stirring and reacting at a constant temperature for 5-9 hours under condensation reflux, then adding hydrocarbon primary amine substances, continuing the constant temperature stirring and reacting for 2-6 hours, centrifuging, washing the separated solid with anhydrous ethanol for 2-4 times, and naturally drying to obtain the modified reinforced fiber; The hydrocarbon primary amine substance is one of dodecyl primary amine, tetradecyl primary amine, hexadecyl primary amine, 7-octen-1-amine, 2-cyclohexene-1-amine, and 1-amino-10-undecene; The modified styrene-butadiene-styrene block copolymer has a preparation method comprising: cutting the styrene-butadiene-styrene block copolymer into small pieces, placing the pieces in a 50-75°C oven for drying for 10-16 hours, transferring the pieces to a reactor, replacing the air in the reactor with nitrogen, and maintaining the nitrogen protection state, adding toluene to the reactor, starting stirring, and adding 2-octenyl succinic anhydride after the styrene-butadiene-styrene block copolymer is completely dissolved, then controlling the stirring rate to 400-1000 rpm, raising the temperature of the material in the reactor and keeping the temperature constant at 70-85°C, adding benzoyl peroxide, stirring the reaction at a constant temperature for 4-7 hours, adding hydroquinone to terminate the reaction, continuing stirring and cooling the material in the reactor to room temperature, adding a precipitant, anhydrous ethanol, stirring for 30-60 minutes, filtering the discharged material, washing the filtered solid with a detergent, anhydrous ethanol, for 2-3 times, and drying naturally to obtain the modified styrene-butadiene-styrene block copolymer; The styrene-butadiene-styrene block copolymer has a melt flow index of 2-10 g / min at 200° C. and 5 kg, and a viscosity of a 25 wt% toluene solution thereof at 25° C. is 2000-6000 cps at 25° C.; The preparation method of the liquid rubber-coated lignin particles is as follows: after drying lignin powder at 100-130°C for 8-15 hours, putting the powder into a high-speed dispersion kettle, then adding toluene and polyoxyethylene cetyl alcohol ether, controlling the dispersion rate at 8000-13000 rpm, dispersing at high speed for 7-12 hours, reducing the dispersion rate to 3000-4500 rpm, then heating and keeping the temperature constant at 75-90°C, then adding diphenylmethane diisocyanate and dibutyltin dilaurate, reacting at the constant temperature for 5-9 hours, then adding liquid rubber, continuing the constant temperature reaction for 4-7 hours, cooling to room temperature, discharging, filtering, washing the filtered solid with anhydrous ethanol for 2-4 times, and drying naturally to obtain liquid rubber-coated lignin particles; The particle size of the lignin powder is 0.5-9 μm; The liquid rubber is hydroxyl-terminated polybutadiene; The hydroxyl-terminated polybutadiene has a hydroxyl value of 0.5-0.8 mmol / g, a viscosity of 3-8 Pa·s at 40° C., and a number average molecular weight of 2.5-4×10 3 g / mol; The modified asphalt for heavy-loaded pavement is prepared by: according to the specific formula of the modified asphalt for heavy-loaded pavement in parts by weight, vegetable oil and rubber powder are first put into a mixing kettle with a high-speed stirring paddle and a high-speed dispersing paddle, heated to 130-180°C, the high-speed dispersing paddle is turned on, the shearing and dispersing rate is controlled at 6000-10000 rpm, after the shearing and dispersing treatment for 100-180 minutes, the high-speed dispersing paddle is stopped, the high-speed stirring paddle is turned on, the stirring rate is controlled at 1000-2500 rpm, road petroleum asphalt is added, and after the road petroleum asphalt is all After melting, stop the high-speed stirring paddle, start the high-speed dispersing paddle, control the shear dispersion rate at 6000-10000 rpm, continue the shear dispersion treatment for 80-150 minutes, stop the high-speed dispersing paddle, start the high-speed stirring paddle, control the stirring rate at 2000-4500 rpm, add modified reinforcing fiber, modified styrene-butadiene-styrene block copolymer and liquid rubber coated lignin particles, continue stirring for 10-20 hours, cool to 65-85°C and then discharge, cool to room temperature after discharging to obtain modified asphalt for heavy-load pavement.

2. The modified asphalt mixture for heavy-load pavement according to claim 1, characterized in that: The sepiolite fiber has a diameter of 4 to 15 μm and a length of 3 to 15 mm; The diameter of the calcium sulfate whisker is 1-10 μm and the length is 40-400 μm; The mass ratio of the sepiolite fiber, calcium sulfate whisker, toluene, polyoxyethylene sorbitan fatty acid ester, diphenylmethane diisocyanate, dibutyltin dilaurate, and hydrocarbon primary amine substances is 30-90:6-20:150-220:1-2.5:6-18:0.2-0.8:5-15.

3. The modified asphalt mixture for heavy-load pavement according to claim 1, characterized in that: The mass ratio of the lignin powder, toluene, polyoxyethylene cetyl alcohol ether, diphenylmethane diisocyanate, dibutyltin dilaurate and liquid rubber is 40-90:150-300:1-5:15-50:0.3-0.9:8-20.

4. The method for preparing a modified asphalt mixture for heavy-load pavement according to claim 1, characterized in that: The preparation method of the modified asphalt mixture for heavy-duty pavement is as follows: aggregates are graded and mixed in advance, and then the modified asphalt for heavy-duty pavement is added into a mixing kettle, and the stirring rate is controlled at 500-1000 rpm, and the asphalt in the kettle is heated and kept at a constant temperature of 150-190° C., and then the aggregates are added into the mixing kettle at a mass ratio of the modified asphalt for heavy-duty pavement to the aggregate of 6-13:100, and after stirring and mixing for 2-5 hours, the modified asphalt mixture for heavy-duty pavement directly used for pavement paving is obtained by discharging the material.

Citation Information

Patent Citations

  • Bituminous mixture for heavy-load transportation road surface and preparation technology of bituminous mixture

    CN109761541A

  • Asphalt mixture suitable for heavy-duty traffic pavement and heavy-duty pavement construction method

    CN116161903A

Cited By

  • Cold-mixed full-steel-slag asphalt mixture and preparation method thereof

    CN122233690A